Efektivitas Model Pembelajaran PBL dan Kolaboratif Melalui Media Googleclassroom Terhadap Hasil Kognitif Siswa Kelas XI SMA N 1 Wadaslintang - Taranggana Lelana Widha; Dani Slamet Pratama; Maftukin Hudah (YLPK Mahardhika, 2022)
Taranggana Lelana Widha. “The effectiveness of the Problem Based Learning and Collaborative learning model through google classroom on the learning outcomes of volleyball subjects for class XI SMA N 1 Wadaslintang”. Thesis of faculty of social sciences and sports education. PGRI Semarang University. 2021. Entering March 2020, a coronavirus pandemic or Covid-19 occurred, forcing all schools to be closed from face-to-face learning, and requiring online learning or learning from home. This means that both teachers and educators must be creative to overcome learning problems during this pandemic. There are so many methods used by teachers so that learning continues and the material is conveyed to students. One of the distance learning media that can be used is google classroom. In the study, the experimental class and the control class were given a pre-test to determine the initial state. After it was known that the two classes were the same/homogeneous, then the experimental class was given treatment with Problem Based Learning and Collaborative learning models, while the control class carried out learning as usual. The study was conducted at SMA N 1 Wadaslintang in 2 classes. Based on the results of the study, it can be concluded that there are significant differences in student learning outcomes who are taught using the Problem Based Learning and google classroom-based Collaborative models on the volleyball learning outcomes in class XI SMA N 1 Wadaslintang because of Sig. (2-tailed) < (0.000 < 0.05). These results mean that the hypothesis is accepted, so that the hypothesis states that problem-based learning and google classroom-based collaborative learning are effective on volleyball learning outcomes in class XI SMA N 1 Wadaslintang. Because there is an influence of problem-based learning and google classroom-based collaborative models on volleyball learning outcomes in class XI students, it is recommended to develop a problem-based learning and collaborative learning model based on google classroom, so that the results obtained which is valid and can improve the effectiveness of student learning.